Individualism vs. collectivism implications for health promotion.[article]. - Pentecostes, Joy U.
This paper examine the strengths and limitations of various health promotion strategies as they relate to individualism-collectivism is discussed in relation to the types of strategies of adopted for improving health: active vs passive measures, the strategies of education, engineering and enforcement. Findings on individualism vs, collectivism in the area of communication research are applied to the health promotion domain. It is hoped that the conceptual framework presented in this paper would contribute to the development of culturally appropriate health promotion interventions.